Life-after-death: exploring thermal annealing conditions to enhance 3D NAND SSD endurance - Buddhanoy, Matchima, author; Pasricha, Sudeep, author; Ray, Biswajit, author; ACM, publisher (Colorado State University. Libraries, 2024)
In this paper, we evaluate thermal annealing effects on the endurance of commercial off-the-shelf (COTS) 3D NAND flash memory beyond its end-of-life. We systematically evaluate the effects of anneal duration, anneal temperature, and state of the memory cells during annealing on the endurance enhancement. Interestingly, we find that endurance enhancement critically depends on the state of flash memory cells during annealing, with programmed cells showing significantly larger improvements than erased cells. Our experimental evaluation indicates that the post-cycle data retention property of an annealed chip significantly improves after thermal annealing, resulting in ∼30% endurance recovery. Our results have significant implications for the future wear-leveling algorithms of SSD-based storage systems.
Keywords: flash memories; 3D NAND; annealing